Journalism research in Spain. Analysis of research articles published in Spanish journals over the past 25 years (1990-2014) (Communication & Society, 2017)
This paper analyses the evolution of journalism research in Spain during the past 25 years, in terms of objects of study, research modalities and methodological approaches. A content analysis was designed and applied to a sample of 461 articles published by five renowned Spanish journals in communication research (Anàlisi, Comunicación y Sociedad, Estudios sobre el Mensaje Periodístico, Revista Latina de Comunicación Social and Zer). Findings highlight the focus of journalism research on daily press studies and on the analysis of news content, and also a progressive decreasing interest on the institutional dimensions (journalists, companies, markets, sectoral policies, etc.) and social dimensions (audiences, reception processes, effects and influence, etc.) of journalism. Regarding research modalities, theoretical studies significantly decrease over the period of analysis, until their virtual absence in the last decade. In contrast, empirical research increases, especially in terms of quantitative studies, and evidences some methodological sophistication. The analysis of the results explain this trend in relation to the changes experimented by the academic and research system in Spanish communication studies since 2008, because of the implementation of the Academia programme for the university teaching habilitation by ANECA. This seems to be directing journalism research towards objects and methods that ensure a high curricular profitability